Targeted Capture of Hundreds of Nuclear Genes Unravels Phylogenetic Relationships of the Diverse Neotropical Palm Tribe Geonomateae - Loiseau, Oriane; Olivares, Ingrid; Paris, Margot; de La Harpe, Marylaure; Weigand, Anna; Koubínová, Darina; Rolland, Jonathan; Bacon, Christine D.; Balslev, Henrik; Borchsenius, Finn; Cano, Angela; Couvreur, Thomas L. P.; et al. (Frontiers in Plant Science, 2019)
The tribe Geonomateae is a widely distributed group of 103 species of Neotropical palms which contains six ecologically important understory or subcanopy genera. Although it has been the focus of many studies, our understanding of the evolutionary history of this group, and in particular of the taxonomically complex genus Geonoma, is far from complete due to a lack of molecular data. Specifically, the previous Sanger sequencing-based studies used a few informative characters and partial sampling. To overcome these limitations, we used a recently developed Arecaceae-specific target capture bait set to undertake a phylogenomic analysis of the tribe Geonomateae. We sequenced about 4,000 genes for 85% of the species of the tribe, including 84% of the species of the largest genus, Geonoma. Phylogenetic relationships were inferred using both concatenation and coalescent methods. Overall, our phylogenetic tree is highly supported and congruent with taxonomic delimitations although several morphological taxa were revealed to be non-monophyletic. It is the first time that such a large genomic dataset is provided for an entire tribe within the Arecaceae. Our study lays the groundwork not only for detailed macro- and micro-evolutionary studies within the group, but also sets a workflow for understanding other species complexes across the tree of life.